2018
DOI: 10.1177/2050640618769713
|View full text |Cite
|
Sign up to set email alerts
|

Individual invitation letters lead to significant increase in attendance for screening colonoscopies: Results of a pilot study in Northern Hesse, Germany

Abstract: Our study clearly indicates that personal invitation letters are an effective measure to increase overall participation rates in screening colonoscopies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…An important element of this reorganized CRC screening system are invitation letters. In fact, several pilot studies conducted in different German federal states demonstrated that the use of CRC screening services can be increased by personal invitation letters [16,17]. However, these and previous studies have demonstrated a major gender-specific difference in utilization of CRC screening in Germany, with significantly lower rates in males than females [11,17,18].…”
Section: Introductionmentioning
confidence: 94%
“…An important element of this reorganized CRC screening system are invitation letters. In fact, several pilot studies conducted in different German federal states demonstrated that the use of CRC screening services can be increased by personal invitation letters [16,17]. However, these and previous studies have demonstrated a major gender-specific difference in utilization of CRC screening in Germany, with significantly lower rates in males than females [11,17,18].…”
Section: Introductionmentioning
confidence: 94%
“…Substantial efforts have been made to increase screening participation. This includes pre-announcement letters, personal invitation that includes the FIT, and reminder letters for FIT testing or personal invitations for OC, all of which have led to a higher screening adherence 5 6 7 . Further increase in screening adherence could potentially reduce the incidence of and mortality from CRC 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Efforts that involve direct patient contact, such as patient navigators or nurses with face-to-face counselling are the most effective [7]. This is also paramount for increasing adherence to colonoscopy screening programs [8].…”
mentioning
confidence: 99%